MicroRNA-146a: a key regulator of astrocyte-mediated inflammatory response. - Anand Iyer (Public Library of Science (PLoS), 2012)
Increasing evidence supports the involvement of microRNAs (miRNA) in the regulation of inflammation in human neurological disorders. In the present study we investigated the role of miR-146a, a key regulator of the innate immune response, in the modulation of astrocyte-mediated inflammation. Using Taqman PCR and in situ hybridization, we studied the expression of miR-146a in epilepsy-associated glioneuronal lesions which are characterized by prominent activation of the innate immune response. In addition, cultured human astrocytes were used to study the regulation of miR-146a expression in response to proinflammatory cytokines. qPCR and western blot were used to evaluate the effects of overexpression or knockdown of miR-146a on IL-1β signaling. Downstream signaling in the IL-1β pathway, as well as the expression of IL-6 and COX-2 were evaluated by western blot and ELISA. Release several cytokines was evaluated using a human magnetic multiplex cytokine assay on a Luminex® 100™/200™ platform. Increased expression of miR-146a was observed in glioneuronal lesions by Taqman PCR. MiR-146a expression in human glial cell cultures was strongly induced by IL-1β and blocked by IL-1β receptor antagonist. Modulation of miR-146a expression by transfection of astrocytes with anti-miR146a or mimic, regulated the mRNA expression levels of downstream targets of miR-146a (IRAK-1, IRAK-2 and TRAF-6) and the expression of IRAK-1 protein. In addition, the expression of IL-6 and COX-2 upon IL-1β stimulation was suppressed by increased levels of miR-146a and increased by the reduction of miR-146a. Modulation of miR-146a expression affected also the release of several cytokines such as IL-6 and TNF-α. Our observations indicate that in response to inflammatory cues, miR-146a was induced as a negative-feedback regulator of the astrocyte-mediated inflammatory response. This supports an important role of miR-146a in human neurological disorders associated with chronic inflammation and suggests that this miR may represent a novel target for therapeutic strategies.